1995
DOI: 10.1080/00221309.1995.9921217
|View full text |Cite
|
Sign up to set email alerts
|

Colors and Emotions: Preferences and Combinations

Abstract: Within three age groups (7-year-old children, 11-year-old children, and adults), preferences for colors and emotions were established by means of two distinct paired-comparison tasks. In a subsequent task, participants were asked to link colors to emotions by selecting an appropriate color. It was hypothesized that the number of times that each color was tied to a specific emotion would be predictable from the separate preferences for colors and emotions. Within age groups, participants had consistent preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
1
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 17 publications
6
111
1
6
Order By: Relevance
“…Valdez and Mehrabian (1994) reported the difficulty of drawing conclusions related to the effect of personality and psychopathology from the available studies for them because of methodology weakness and invalidity of the measures used in these studies (from their view) (Valdez & Mehrabian, 1994). Terwogt and Hoeksma (1995) indicated that the relationship between colours and emotions (categorised by negative, positive and no) could be explained on the basis of preference.…”
Section: Effect Of Gendermentioning
confidence: 99%
See 3 more Smart Citations
“…Valdez and Mehrabian (1994) reported the difficulty of drawing conclusions related to the effect of personality and psychopathology from the available studies for them because of methodology weakness and invalidity of the measures used in these studies (from their view) (Valdez & Mehrabian, 1994). Terwogt and Hoeksma (1995) indicated that the relationship between colours and emotions (categorised by negative, positive and no) could be explained on the basis of preference.…”
Section: Effect Of Gendermentioning
confidence: 99%
“…Differences in both subjective experiences and environmental reactions contributed to the changing preference for fear and anger at different ages. Besides people opinion would differ due to different experience (Terwogt & Hoeksma, 1995).…”
Section: Colour Emotion As a Function Of Preferencementioning
confidence: 99%
See 2 more Smart Citations
“…red orange, yellow. As for gender difference, both males and females showed highest affinity for blue followed by green hues [19].…”
Section: Introductionmentioning
confidence: 99%